TINJAUAN YURIDIS TERHADAP PERTANGGUNGJAWABAN PELAKU USAHA YANG MENJUAL PRODUKNYA DENGAN SISTEM PENJUALAN LANGSUNG/DIRECT SELLING (Studi Kasus Pada Perusahaan PT.Harmoni Dinamik Indonesia) - ANGFIER A SINAGA (JURNAL CIVIL LAW USU, 2013)
Abstract : Direct Sales System's common we hear today by selling a variety of goods and / or services they offer to consumers. Begins with a controversial past, resulting in a no-confidence among the public as consumers. A lot of people questioned whether direct sales system is really beneficial that does not pose a risk to consumers. The problems that existed for this will be discussed in this thesis with the title Against Judicial Accountability Overview Business communities Selling products with Direct Sales System. Discussion of how the provision of direct sales by the Minister of Trade. No. 32/M-DAG/PER/8/2008, businessmen responsibility for products sold by direct sales system, and the way the settlement is done in case of disputes between businesses and consumers.   Keywords : Direct Sales System’s